Covalent immobilization of a-amylase onto thermally crosslinked electrospun PVA/PAA nanofibrous hybrid membranes - KAHRAMAN, MEMET VEZİR; DANIŞ, ÖZKAN; DEMİR, SERAP (WILEY, 2013)
Poly(vinyl alcohol)/poly(acrylic acid) (PVA/PAA) nanofibers with the fiber diameter of 100150 nanometers were fabricated by electrospinning. PVA/PAA nanofibers were crosslinked by heat-induced esterification and resulting nanofiber mats insoluble in water. a-Amylase was covalently immobilized onto the PVA/PAA nanofiber surfaces via the activation of amine groups in the presence of 1,1'-carbonyldiimidazole. The immobilized a-amylase has more resistance to temperature inactivation than that of the free form and showed maximum activity at 50 degrees C. pH-dependent activities of the free and immobilized enzymes were also investigated, and it was found that the pH of maximum activity for the free enzyme was 6.5, while for the optimal pH of the immobilized enzyme was 6.0. Reuse studies demonstrated that the immobilized enzyme could reuse 15 times while retaining 81.7% of its activity. Free enzyme lost its activity completely within 15 days. Immobilized enzyme lost only 17.1% of its activity in 30 days. (C) 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012
Keywords: nanofiber; PVA; PAA; amylase; immobilization; electrospun; ALPHA-AMYLASE; ENZYMES; SURFACE; STABILITY; SUPPORT; BEADS